Hybrid Power System for Power Quality Improvement and Security Analysis - Kumar Mishra, Ajay; Mishra, Bharat; Sharma, A. K (International Journal of Computer Sciences and Engineering, 2025)
The generation of electricity through renewable sources has exponentially increased in recent years in response to environmental pollution caused by fossil fuels. When we talk about renewable energy is difficult not to refer to solar energy, wind energy, biomass energy and Pedal generation due to its high rate of growth compared to their peers and potential. This is associated with the fact that the government is implementing a process of changing the production of energy and country's energy matrix where one of the fundamental pillars is to eliminate dependence on fossil resources and promote the use of renewable energy especially for rural areas. Therefore, this makes clear that it is important and needed to study the effects and possible problems related to renewable energy that entails the use of photovoltaic systems connected to the network with hybrid one like pedal system generation which is easily available. In this context, the work focuses on power quality by connecting photovoltaic to low-power electrical system with using solar and pedal generation simultaneously. Objective of this research based on other sources of energy i.e. renewable energy, because we have limited sources of non renewable sources of energy i. e. coal diesel, petrol etc. Energy crises need to search for other source of energy that is specifically renewable energy. Human power praise is more because of health benefit as a source of energy. And in this peoples are more aware to his health point of view. More effective use of human power could be achieved through properly design approach. Human power as prime mover used to operate working unit is termed as human powered machine (bicycle) and this machine is different from conventional bicycle because it can operate with different arrangement with the help of hand or leg or in special case with the help of animal power and in developed machine combination of gear arrangement and chain are used. In this paper two models are simulated one .